Etnomatematika alat musik tradisional saron laras pelong dan kaitannya dengan konsep peluang - Fitriani, Hanifah (Maliki Interdisciplinary Journal, 2024)
In this rapidly changing era, the interests and knowledge of the younger generation are quite limited. If this situation is allowed to persist, it is undeniable that our cultural heritage may also be lost. Ethnomathematics, as a mathematical concept that encompasses cultural elements and can be utilized in education, is expected to address this issue. This research was conducted to explore ethnomathematics within the traditional musical instrument Saron Laras Pelong and its relevance to the concept of probability in mathematics education. The study utilized ethnographic methods, in which the researcher primarily conducted a literature review by examining various references. The results obtained from this research indicate the presence of ethnomathematics in the traditional musical instrument Saron Laras Pelong and its connection to the concept of probability. Therefore, the traditional musical instrument Saron Laras Pelong can be employed in mathematics education to make it more meaningful while also serving as a means to preserve and introduce Indonesian culture.